Damage, diversity and genetic vulnerability: The role of crop genetic diversity in the agricultural production system to reduce pest and disease damage: Proceedings of an International Symposium 15-17 February 2011, Rabat, Morocco - Jarvis, Devra I.; Fadda, Carlo; Santis, P. de; Thompson, J.; Bioversity International (2011)
Integrated Pest Management (IPM) is a widely recognized ecosystem approach to crop production and protection that combines different management strategies and practices to grow healthy crops and minimize the use of pesticides. However, IPM methods have until recently made limited use of intra-specific diversity to manage pests and diseases. The chapters in this volume are based on results from research which began in 2002, to collect standardized information from farmers on crop varietal diversity, sources of traditional and modern planting materials, and disease management practices that related to crop varietal diversity.